PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE, DAN KARAKTERISTIK PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Astrid Dini Aliyani; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2023)
This study examines the relationship between corporate social responsibility, corporate governance, and firm characteristics with the level of tax avoidance in manufacturing companies.  This study uses tax avoidance as the dependent variable and corporate social responsibility, corporate governance, and firm characteristic (capital intensity) as independent variables. Also, leverage, profitability, and firm size as control variables. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange period 2017-2021. Using purposive sampling, 85 samples were obtained for 5 consecutive years. This study uses multiple linear regression analysis to test the hypothesis. The finding from this study proves that corporate social responsibility and corporate governance have a significant negative relationship to the extent of tax avoidance. While capital intensity has no significant relationship to the extent of tax avoidance.